Proceedings. 7th International Workshop on Principles of Software Evolution, 2004.
DOI: 10.1109/iwpse.2004.1334772
|View full text |Cite
|
Sign up to set email alerts
|

Aiding comprehension of cloning through categorization

Abstract: Management of duplicated code in software systems is important in ensuring its graceful evolution. Commonly clone detection tools return large numbers of detected clones with little or no information about them, making clone management impractical and unscalable. We have used a taxonomy of clones to augment current clone detection tools in order to increase the user comprehension of duplication of code within software systems and filter false positives from the clone set. We support our arguments by means of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…They found that the percentage of cloned code did not change during software evolution and that, while new clones were added, some were factored out. Kasper and Godfrey [27] proposed a classification of clones based on their distance, i.e., within the same function, or file, or directory, and based on their granularity, i.e., block, function, or file. They used such a classification on clones detected in the Linux Kernel.…”
Section: Empirical Studies On the Presence And Evolution Of Clonesmentioning
confidence: 99%
“…They found that the percentage of cloned code did not change during software evolution and that, while new clones were added, some were factored out. Kasper and Godfrey [27] proposed a classification of clones based on their distance, i.e., within the same function, or file, or directory, and based on their granularity, i.e., block, function, or file. They used such a classification on clones detected in the Linux Kernel.…”
Section: Empirical Studies On the Presence And Evolution Of Clonesmentioning
confidence: 99%
“…It is suspected that approximately 10%-15% of many large systems is part of duplicated code [2,12,24,25], and it has been documented to exist at rates of over 50% of the effective lines of code (ELOC) in a particular COBOL system [12]. The literature on the topic has described many situations that can lead to the duplication of code within a software system [2,7,21,22,27,28].…”
Section: Code Cloningmentioning
confidence: 99%
“…During our investigations of cloning in large software systems [23,24,25], we found several recurring patterns of cloning, or rather ways in which developers duplicated behavior. These patterns are defined by what is duplicated and why, and to some extent how the duplication is done.…”
Section: Patterns Of Cloningmentioning
confidence: 99%
See 2 more Smart Citations